Evaluation of severity level, stress, and bad habit among dental students with exfoliative cheilitis - Sivabalasundram, Sangary Sri; Herawati, Erna; Yohana, Winny (Universitas Padjadjaran, 2022)
Introduction: Exfoliative cheilitis (EC) is one of the most common cheilitis found in the community. This lesion can cause difficulty in mouth opening, speech difficulties, and reduced aesthetical value of the lips. EC is a chronic inflammation characterised by desquamation, erythema, and crusting on the upper or lower lip. This study evaluated severity level, stress, and bad habit among dental students with exfoliative cheilitis. Methods: The method used in this research was descriptive with a total sampling method on the populations of dental students batch of 2016 to 2018 of the Faculty of Dentistry Universitas Padjadjaran, which obtained 83 dental students with EC. The lips were then examined, and data was recorded. EC was classified into three stages in clinical manifestation: mild, moderate, and severe exfoliative cheilitis. The data were presented with a simple frequency distribution table. Result: 30.1% of the research subjects had mild EC, 53% had moderate EC, and 16.9% had severe EC. The predisposing factors of EC in this research were stress and bad habits, where the percentage contribution were 53% and 16.9%, respectively. Students were also found with both stress and bad habits with a percentage contribution of 30.1%. Conclusions: Moderate exfoliative cheilitis is most commonly found with desquamation and erythema clinical features. The predisposing factor of exfoliative cheilitis is stress which has the highest percentage among dental students.